KORELASI FAKTOR IBU TERHADAP KEJADIAN STUNTING PADA ANAK USIA 0-59 BULAN - Anwar, Seniwaty; Sutiswa, Shandra Isasi; Primasari, Yefta; Siddiq, Muhammad Nuzul Azhim Ash; Apidianti, Sari Pratiwi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Stunting, or short stature, is a common nutritional problem among children in many countries. Stunting refers to chronic malnutrition that results in a child's height not being appropriate for their age. The Geragai area is the area with the highest incidence of stunting in Jambi City, namely 262 children aged 0-59 months who are stunted with a prevalence of 24.58%. The purpose of the study was to determine the correlation of maternal factors with the incidence of stunting in children aged 0-59 months. This type of research is quantitative with a cross sectional approach. The sample amounted to 73 people. The sampling technique used Stratified Proportional Sampling. The results showed that there was a relationship between maternal knowledge (p value: 0.000) and the incidence of stunting. It is expected that the Puskesmas can increase public knowledge through preventive actions and health promotion to the community and conduct counseling to cadres in each village, then increase breastfeeding counseling to pregnant women, adolescents, or prospective brides.Keywords: Toddlers, Maternal Knowledge, Stunting